Recommendations for the Implementation of ISO 9001:2015 in the Manufacturing Industry of Pakistan - Khan, Z.; Yusof, Y. B.; Abass, N. H. B.; Ahmed, M. B. I.; Jamali, Q. B. (Engineering, Technology & Applied Science Research, 2021)
ISO 9001:2015 is known as the highest quality management standard, enhancing customer and company satisfaction. While the manufacturing industry is playing a vital role in Pakistan’s GDP, the implementation of ISO 9001:2015 is not widespread. This study aims to examine the factors that hinder the implementation of ISO 9001:2015 in Pakistan’s manufacturing industry and recommend suggestions to overcome them. An in-depth literature review identified 32 general factors that hinder the implementation of ISO 9001:2015. A structured questionnaire was designed and distributed to 135 respondents to examine the factors hindering the implementation of ISO 9001:2015 in Pakistan’s manufacturing industry. The gathered data were analyzed using the average index formula, and 8 significant factors were identified. These factors were used in the design of a semi-structured questionnaire distributed among high qualified and experienced respondents working in top managerial posts of manufacturing industries in Pakistan. The collected data were analyzed using content analysis. The findings can be helpful in the determination of recommendations regarding the implementation of ISO 9001:2015 in the manufacturing industries of Pakistan.